Organisasi Profesi Guru dalam Penguatan Mutu Pendidikan: Analisis Kelembagaan atas PGRI, IGI, MGMP, dan KKG - Farrel Aditya Hermawan; Annisa Putri Alamsyah; Elfridana Sinta Marito; Frasya Titranissa; Gheannysa Alishanaya (Saneskara: Journal of Social Studies, 2026)
Teacher professional organizations hold a strategic position in enhancing educator professionalism and supporting the educational quality assurance system. However, their institutional effectiveness remains constrained by the dominance of administrative routines and weak systemic coordination. This article aims to analyze the roles, challenges, and institutional relevance of PGRI, IGI, MGMP, and KKG in strengthening educational quality in Indonesia through a Total Quality Management (TQM) perspective. Employing a qualitative approach with a descriptive-analytical literature review method, this study systematically differentiates the functions of policy advocacy (PGRI), digital innovation (IGI), and pedagogical reflection in professional learning communities (MGMP/KKG). The findings indicate that repositioning professional organizations as quality assurance agents can be achieved through organic interventions in the PPEPP cycle driven by the utilization of Educational Report Cards (Rapor Pendidikan) data. This study recommends the integration of member databases and regulatory synchronization following the enforcement of Permendikbudristek Number 67 of 2024.